The Role of Managerial Efficiency in Enhancing Economic Value Added (EVA) and Firm Competitiveness - Ahmad, Ahmad (Indonesian Research Journal on Education, 2025)
This study investigates the role of managerial efficiency in enhancing Economic Value Added (EVA) and improving firm competitiveness within the context of modern corporate performance measurement. Managerial efficiency, defined as the optimal utilization of organizational resources to achieve maximum output with minimal waste, is hypothesized to have a direct and indirect influence on the creation of shareholder value and the firm’s market positioning. Using a quantitative research library research, this study employs Data Envelopment Analysis (DEA) to measure managerial efficiency across a sample of listed companies, while EVA serves as a financial performance indicator reflecting the firm’s ability to generate value beyond its cost of capital. The findings are expected to demonstrate that firms exhibiting higher managerial efficiency tend to achieve superior EVA outcomes, which subsequently lead to enhanced competitiveness in both domestic and international markets. Moreover, the study emphasizes the strategic implications of efficient management practices, highlighting their contribution to sustainable value creation and long-term corporate resilience. These results underscore the importance of managerial capability as a critical determinant of financial and strategic success, offering insights for executives and policymakers aiming to strengthen organizational performance in dynamic economic environments.